Perspectives for Forkhead box transcription factors in diabetic cardiomyopathy: Their therapeutic potential and possible effects of salvianolic acids - Han, Ronghui; Huang, Hemeng; Xia, Weiyi; Liu, Jingjin; Luo, Hui; Tang, Jing; Xia, Zhengyuan (Frontiers in Cardiovascular Medicine, 2022)
Diabetic cardiomyopathy (DCM) is the primary cause of morbidity and mortality in diabetic cardiovascular complications, which initially manifests as cardiac hypertrophy, myocardial fibrosis, dysfunctional remodeling, and diastolic dysfunction, followed by systolic dysfunction, and eventually end with acute heart failure. Molecular mechanisms underlying these pathological changes in diabetic hearts are complicated and multifactorial, including but not limited to insulin resistance, oxidative stress, lipotoxicity, cardiomyocytes apoptosis or autophagy, inflammatory response, and myocardial metabolic dysfunction. With the development of molecular biology technology, accumulating evidence illustrates that members of the class O of Forkhead box (FoxO) transcription factors are vital for maintaining cardiomyocyte metabolism and cell survival, and the functions of the FoxO family proteins can be modulated by a wide variety of post-translational modifications including phosphorylation, acetylation, ubiquitination, arginine methylation, and O-glycosylation. In this review, we highlight and summarize the most recent advances in two members of the FoxO family (predominately FoxO1 and FoxO3a) that are abundantly expressed in cardiac tissue and whose levels of gene and protein expressions change as DCM progresses, with the goal of providing valuable insights into the pathogenesis of diabetic cardiovascular complications and discussing their therapeutic potential and possible effects of salvianolic acids, a natural product.